The Influence of Block Practice and Random Practice on Mastery of a Series of Pencak Silat Team Moves - Yudi Rachman; Indra Safari; Adang Sudrazat; Alifya Ananda Pradana (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
IPSI defined that, "Pencak silat is the result of Indonesian culture to defend, maintain existence ( independence), and integration (unity) with the living environment or natural surroundings in order to achieve harmony in life, in order to increase one's faith and piety to God Almighty." In the athlete's performance, the jury referee makes an assessment where there are several points that the jury will assess, namely the sequence of movements, correctness of movement details, stance technique. If the performance exceeds the tolerance time limit given, a penalty will be imposed (a reduction of 10 points) and the participant will be disqualified if he cannot continue the performance due to his mistake. Researchers used two research methods to see a comparison of the results of the training methods that had been carried out. So the title of this research is "The Influence of Block Practice and Random Practice Training Methods on Mastery of the Movement Series of Pencak Silat Team Moves in Cirebon City".The experimental method is a research design that refers to the problem at hand, and looks at the cause and effect of a treatmentthat "the aim of an experiment is to investigate whether or not there is a cause-and-effect relationship. cause-and-effect relationship by administering certain treatments to several experimental groups and providing controls for comparison.” In this research, the method used will be to test (validate) one or more research variables against other variables. In this research design, researchers used 2 groups, where 1 group would be given random practice treatment and 1 group would be given block practice treatment.